Publication patterns in the social sciences and humanities in Flanders and Poland - Kulczycki, Emanuel; Engels, Tim C.E.; Nowotniak, Robert (My University, 2017)
This paper investigates internationalization patterns in the language and type of social sciences and humanities publications in non-English speaking countries. This research aims to demonstrate that such patterns are related not only to discipline but also to each country’s cultural and historic heritage. We used data from Flemish and Polish databases collected between 2009 and 2014. In Flanders, on the one hand, we found that changes in the use of languages and publication types were moderate and occurred gradually over several years. In Poland, on the other hand, we found significant shifts in the use of certain publication types, sometimes from year to year. Examining the social sciences and humanities literature both as a whole and broken down by discipline, we observed similar variability over time in the proportion of work published in English and in article form. However, we found remarkable differences between Flanders and Poland regarding the most commonly used languages and publication types. Overall, we found few similarities between Flemish and Polish social sciences and humanities publication patterns.
The authors would like to thank Ewa A. Rozkosz for her useful suggestions and remarks.
Keywords: Flanders; Poland; publication patterns; social sciences; humanities; research evaluation